Tendances actuelles en chimie analytique : applications et perspectives. - DJARI , Dounia Malek; BENDALI , Mostefa Hayem; GUEMMAZ , Serine; KAARAR , Mohamed Nadjib (Encadrant) (Université Sétif1 Ferhat Abbas. Faculté de Médecine. Déppartement de Pharmacie, 2025)
Analytical chemistry, as a fundamental pillar of experimental sciences, is undergoing a profound transformation driven by emerging technologies. This thesis explores the growing contributions of nanotechnology, the miniaturization of analytical devices, notably through Lab-on-a-Chip (LOC) technology and artificial intelligence in the evolution of chemical analysis methods. These innovative approaches promise significant improvements in sensitivity, speed, and precision. They also allow for the processing of smaller sample volumes, the reduction of human error, and the exploitation of complex data through advanced algorithms. However, the reliability, reproducibility, and economic viability of these technologies remain major challenges compared to well-established classical methods such as HPLC or TLC. This work offers a comparative analysis of these two paradigms traditional and innovative in order to assess the real potential of integrating modern technologies into analytical practice. The findings suggest that rather than replacing conventional methods outright, these innovations follow a complementary logic, shaping a hybrid form of analytical chemistry that is better suited to the scientific, environmental, and medical challenges of the modern era.
Keywords: Nanotechnologie; Nanomatériau; Lab-on-a-chip; Microfluidique; Intelligence Artificielle.